Determination of Tax Avoidance in Property and Real Estate Companies Listed on the Indonesia Stock Exchange: Analysis of Profitability, Leverage and Company Size (Literature Review Study) - Widyastuti, Tri (Green Publisher, 2026)
Tax avoidance practices are a crucial issue in the tax system because companies often exploit regulatory loopholes to minimize their tax liabilities without directly violating the law. This study aims to analyze the determinants of tax avoidance in property and real estate companies listed on the Indonesia Stock Exchange by examining the influence of profitability, leverage, and company size through a literature review approach. The research method used is a qualitative approach with a literature study technique that examines various relevant previous studies. The type of data used is secondary data obtained from various reputable scientific publication sources, such as journals indexed by Elsevier, Sage, Springer, Web of Science, Ebsco, Copernicus, Sinta, and Google Scholar. Data analysis is carried out descriptively qualitatively through the process of identification, review, and synthesis of previous research findings related to the variables of tax avoidance, profitability, leverage, and company size. The results of the study indicate that profitability, leverage, and company size have an influence on tax avoidance behavior in property and real estate companies.